Coastal Research Seen Through an Early Career Lens—A Perspective on Barriers to Interdisciplinarity in Norway - Deininger, Anne; Martin, Angela H.; Pardo, Juan C. F.; Berg, Paul R.; Bhardwaj, Jyotirmoy; Catarino, Diana; Fernández-Chacón, Albert; Martinez-Swatson, Karen; Ono, Kotaro; Oomen, Rebekah A.; Sodeland, Marte; Sørdalen, Tonje Knutsen; et al. (Frontiers in Marine Science, 2021)
The value of interdisciplinarity for solving complex coastal problems is widely recognized. Many early career researchers (ECRs) therefore actively seek this type of collaboration through choice or necessity, for professional development or project funding. However, establishing and conducting interdisciplinary research collaborations as an ECR has many challenges. Here, we identify these challenges through the lens of ECRs working in different disciplines on a common ecosystem, the Norwegian Skagerrak coast. The most densely populated coastline in Norway, the Skagerrak coast, is experiencing a multitude of anthropogenic stressors including fishing, aquaculture, eutrophication, climate change, land runoff, development, and invasive species. The Skagerrak coastline has also been the focus of environmental science research for decades, much of which aims to inform management of these stressors. The region provides a fantastic opportunity for interdisciplinary collaboration, both within and beyond the environmental sciences. This perspective article identifies the barriers ECRs in Norway face in establishing interdisciplinary and collaborative research to inform management of coastal ecosystems, along with their root causes. We believe our discussion will be of broad interest to all research institutions who employ or educate ECRs (in Norway and worldwide), and to those who develop funding mechanisms for ECRs and interdisciplinary research.